Reformulasi Kurikulum Sarjana Bisnis Digital di Indonesia - Iswanda F. Satibi; Iqbal Ramadhani Mukhlis; Nambi Sembilu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to map and analyze the Digital Business Education (DBE) curricula across Indonesian universities, identifying thematic emphases and assessing differences between public and private institutions. It seeks to understand how well these programs align with industry needs and accreditation standards. A quantitative, descriptive study was conducted. Using Open-Government-Data from the Ministry of Education (Sept–Oct 2024), we harvested programme‐level and course-level information for all 298 DBE offerings. Cleaned course descriptions (n ≈ 19,000) underwent bilingual content analysis and Latent Dirichlet Allocation to expose latent themes. Credit loads were compared with t-tests, and a logistic-regression classifier based on topic weights predicted institutional ownership; performance was assessed with ROC‐AUC. Private universities deliver 91.8 % of DBE programmes (223 bachelor, 44 diploma), whereas public institutions offer 20 bachelor and 11 diploma tracks. Six dominant curriculum clusters emerged—Analytical Operations (marginal P = 0.198), Tech Governance (0.170), Foundational Values (0.162), Entrepreneurial Marketing (0.154), Applied Systems (0.157) and Advanced Projects (0.158). Average course credits were slightly higher in public universities (3.00 ± 1.77) than in private ones (2.81 ± 1.28). The topic-based model distinguished private from public curricula with AUC 0.82 (training) and 0.80 (validation); Entrepreneurial Marketing and Applied Systems strongly signalled private ownership, while Foundational Values and Analytical Operations typified public provision. This research is the first nation-level audit of Indonesia's DBE programs, offering crucial insights into curriculum trends and discrepancies between private and public universities. The study highlights the imbalance in emerging technologies such as blockchain engineering and UX design, urging a recalibration of curricula to enhance both labor-market readiness and ethical foundations.